The strongman : Vladimir Putin and the struggle for Russia / Angus Roxburgh. - Roxburgh, Angus (London : I. B. Tauris, 2012)
Russia under Vladimir Putin has proved a prickly partner for the West, a far cry from the democratic ally many hoped for when the Soviet Union collapsed. Abroad, Putin has used Russia's energy strength as a foreign policy weapon, while at home he has cracked down on opponents, adamant that only he has the right vision for his country's future.
Includes bibliographical references and index.
Keywords: Putin, Vladimir Vladimirovich, -- 1952-; Presidents -- Russia (Federation) -- Biography; Russia (Federation) -- Politics and government -- 1991-